Psychometric properties of the Malay version of the diabetes empowerment scale among Hospital Serdang type 2 diabetes mellitus patients using exploratory factor analysis - Ching, Siew Mooi; Yee, Anne; Lee, Ping Yein; Ramachandran, Vasudevan; Shum, Khai Mun; Ismael, Nur Fati’Izzati; Wan Sulaiman, Wan Aliaa; Hoo, Fan Kee; Foo, Yoke Loong; Lee, Kai Wei; Danaee, Mahmoud; Tan, Kit Aun (Springer, 2020)
Background: This study was initiated to examine the psychometric components of the Diabetes Empowerment Scale (DES) by translating and validating the scale into the Malay language (DES-M) which is the main language spoken in Malaysia. This study can determine the level of empowerment among diabetic patients towards diabetes management. In addition, the reliability and validity of the DES-M was also demonstrated. Methods: A total of 151 patients with type 2 diabetes mellitus were recruited (between June 2016 and October 2016) to complete sets of questionnaires, which were DES-M, the Malay versions of the Diabetes Quality of Life (DQOL) for Adults and Summary of Diabetes Self Care Activities Questionnaire (SDSCA). Confirmatory and Exploratory factor analysis (CFA and EFA) were carried out to determine the factor structures of the DES-M. Results: There were 100 males and 51 females with ages ranging from 19 to 81 years old (55 ± 13) included in this study. The instrument displayed good internal consistency (Cronbach’s α =0.920) and the respective coefficients ranged from 0.65–0.84. Discriminant validity showed adequate correlations ranged from 0.257–0.744. Concurrent validity with SDSCA (Pearson’s correlation = 0.313, p = 0.012). Predictive validity with DQOL (B = 0.27, p = 0.016). CFA indicated that four factor model of the DES-M has good fit to the data. Conclusion: This study indicates that the DES-M has a good internal consistency and validity. Therefore, it is a valid and reliable instrument for assessing empowerment score among patients with diabetes in Malaysia.